PENERAPAN NETWORK PLANING PADA PEKERJAAN PEMBUATAN ITEM KAPAL TUGBOAT DI PT KARIMUN MARINE SHIPYARD - Hilmy, Zakwan; Risky Adiyanto, Fajar; Dzirrusydi, Zalmi (JURNAL JALASENA, 2024)
Work network planning or also known as network planning is a method used in the manufacture of tugboats. The network planning analysis method used in tugboat shipbuilding in this study is to use the cpm (critical path method) method.The purpose of this research is to find network planning on the work of making tugboat items to find out which activities are crisis paths to minimize delays in the completion of making tugboat items. The type of research used is qualitative research. The research variables used are the creation of a work network, determining the earliest time of the event (eet) and the slowest time of the event (let), the critical path and the completion time of making tugboat items. The type of data used is quantitative data sourced from interviews, observations and company documents. Critical work is an activity: A. (Preparation and Submission of Contracts), B. (Making and Submission of Drawings), C. (Provision of Matrial), E. (Fitting), F. (Fit Up), G. (Checking by Supervisors from the Shipyard), H. (Welding), J. (Blasting), L (Provision and Installation of Fittings).